Rapid Modelling and Quick Response Intersection of Theory and Practice - Reiner, Gerald (Springer London : Imprint: Springer, 2010)
Rapid Modelling and Quick Response is a proceedings volume of selected papers presented at the Second Rapid Modelling Conference "Quick Response - Intersection of Theory and Practice" presents new research developments, as well as business/teaching cases in the field of rapid modelling and quick response linked with performance improvements (based on lead time reduction, etc., as well as financial performance measures). This volume is a sequel to the First Rapid Modelling Conference proceedings volume that focused on rapid modelling for increasing competitiveness. The main focus of this second proceedings volume "Rapid Modelling and Quick Response - Intersection of Theory and Practice" is the transfer of knowledge from theory to practice, providing the theoretical foundations for successful performance improvement. Furthermore, illustrations will be given by teaching/business cases, as well as by success stories about new software tools in this field, and new approaches. The interested reader (researcher, as well as practitioner) will gain a good overview on new developments in this field. This conference volume is a must-have for innovative production managers, as well as for managers of service-providing processes. The theoretical, as well as the empirical/practical, pieces of work presented will change the mindset of the interested reader. Rapid Modelling and Quick Response will also contribute to the scientific communities of operations management, production management, supply chain management, industrial engineering and operations research. This volume and the presented research work, teaching/business cases, as well as software tools, can be also used for the education of students and executive managers. Rapid Modelling and Quick Response is supported by the SEVENTH FRAMEWORK PROGRAMME - THE PEOPLE PROGRAMME - Industry-Academia Partnerships and Pathways Project (No. 217891) "How revolutionary queuing based modelling software helps keeping jobs in Europe. The creation of a lead time reduction software that increases industry competitiveness and supports academic research.".